Degradasi lingkungan dan dampaknya terhadap kegiatan usaha tani di sekitar lokasi pertambangan nikel di Kabupaten Konawe Selatan, Sulawesi Tenggara: Environmental degradation and its impact on agricultural activities around nickel mining sites in South Konawe Regency, Southeast Sulawesi - Maga, La; Salahuddin; Malik, Nurhayu; Marei, Dominggus (Analisis Kebijakan Pertanian, 2025)
Nickel mining activities in Tinanggea Subdistrict, South Konawe Regency, Southeast Sulawesi Province, managed by PT X, have caused negative impacts. This condition occurs due to land conversion and mining waste that pollute the irrigation water sources of rice fields. The purpose of this study is to analyze the impact of environmental degradation on rice farming activities around the nickel mining site. Data collection and analysis were conducted from March to August 2017 using quantitative descriptive analysis methods. Primary data was obtained through interviews with rice field farmers in locations affected by PT X’s nickel mining activities in four villages and unaffected locations in two villages, as a comparison. Based on the study’s results, environmental degradation from nickel mining affects productivity and increases production costs in rice farming. The total loss due to nickel mining is estimated at IDR 498 million per year. To overcome this problem, PT X is recommended to routinely monitor environmental quality outside the nickel mining area, particularly in rice fields, as part of its nickel mining activities. It is recommended that the local government increase supervision and monitoring of mining activities to prevent or minimize adverse impacts on the environment and farming activities.